2018
DOI: 10.3390/cancers10060206
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of STAT3 in Myeloma Cells Cultured in a Three-Dimensional, Reconstructed Bone Marrow Model

Abstract: Malignant cells cultured in three-dimensional (3D) models have been found to be phenotypically and biochemically different from their counterparts cultured conventionally. Since most of these studies employed solid tumor types, how 3D culture affects multiple myeloma (MM) cells is not well understood. Here, we compared MM cells (U266 and RPMI8226) in a 3D culture model with those in conventional culture. While the conventionally cultured cells were present in single cells or small clusters, MM-3D cells grew in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 68 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…STAT3 is also highly expressed in some normal tissues and organs, including the bone marrow, peripheral nervous system, and digestive tract and plays a physiological role [2325]. In the normal physiological conditions, STAT3 phosphorylation and activation are tightly controlled by several intrinsic inhibitors, including protein tyrosine phosphatases (PTPs), the suppressors of cytokine signaling (SOCS), and the protein inhibitor of activated STAT (PIAS) [26].…”
Section: The Stat3 Signaling Pathwaymentioning
confidence: 99%
“…STAT3 is also highly expressed in some normal tissues and organs, including the bone marrow, peripheral nervous system, and digestive tract and plays a physiological role [2325]. In the normal physiological conditions, STAT3 phosphorylation and activation are tightly controlled by several intrinsic inhibitors, including protein tyrosine phosphatases (PTPs), the suppressors of cytokine signaling (SOCS), and the protein inhibitor of activated STAT (PIAS) [26].…”
Section: The Stat3 Signaling Pathwaymentioning
confidence: 99%
“…This compound was demonstrated to selectively inhibit the dimerization and transcriptional activity of STAT3, although a report indicated that it also blocks STAT1 phosphorylation [330]. STATTIC reduced P-Y-STAT3 and viability of MM cells in three-dimensional (3D) culture and sensitized them to bortezomib, a proteasome inhibitor that is clinically used in MM treatment (this issue) [331]. Moreover, STATTIC suppressed growth and survival of NK/T cell lymphoma cell lines expressing the STAT3 Y640F mutant [332].…”
Section: Inhibitors Targeting the Sh2 Domainmentioning
confidence: 99%
“…The method for 3-D culture was adapted from [16]. Briefly, 24-well plates were coated with 200 µL of reconstituted endosteum obtained by a mixture of FBN (77 µg/mL) and collagen I (29 µg/mL).…”
Section: Cell Lines and Culture Modelsmentioning
confidence: 99%